Golgi stress mediates redox imbalance and ferroptosis in human cells. (December 2018) - Alborzinia, Hamed; Ignashkova, Tatiana; Dejure, Francesca; Gendarme, Mathieu; Theobald, Jannick; Wölfl, Stefan; Lindemann, Ralph; Reiling, Jan
Abstract Cytotoxic activities of several Golgi-dispersing compounds including AMF-26/M-COPA, brefeldin A and golgicide A have previously been shown to induce autophagy or apoptosis. Here, we demonstrate that these Golgi disruptors also trigger ferroptosis, a non-apoptotic form of cell death characterized by iron-dependent oxidative degradation of lipids. Inhibitors of ferroptosis not only counteract cell death, but they also protect from Golgi dispersal and inhibition of protein secretion in response to several Golgi stress agents. Furthermore, the application of sublethal doses of ferroptosis-inducers such as erastin and sorafenib, low cystine growth conditions, or genetic knockdown of SLC7A11 and GPX4 all similarly protect cells from Golgi stress and lead to modulation of ACSL4, SLC7A5, SLC7A11 or GPX4 levels. Collectively, this study suggests a previously unrecognized function of the Golgi apparatus, which involves cellular redox control and prevents ferroptotic cell death. Hamed Alborzinia et al. show that Golgi-dispersing compounds trigger iron-dependent oxidative degradation of lipids, inducing a non-apoptotic cell death called ferroptosis. This study provides insight into the role of Golgi apparatus for preventing ferroptotic cell death through its cellular redox control.